Veno-Venous Extracorporeal Membrane Oxygenation for Respiratory Failure: How Long Is Too Long?. Issue 2 (February 2019) - Menaker, Jay; Rabinowitz, Ronald P.; Tabatabai, Ali; Tesoriero, Ronald B.; Dolly, Katelyn; Cornachione, Christopher; Stene, Edward; Buchner, Jessica; Kufera, Joseph; Kon, Zachary N.; Deatrick, Kristopher B.; Herr, Daniel L.; et al.
Abstract : The use of veno-venous extracorporeal membrane oxygenation (VV ECMO) in adults with respiratory failure has steadily increased during the past decade. Recent literature has demonstrated variable outcomes with the use of extended ECMO. The purpose of this study is to evaluate survival to hospital discharge in patients with extended ECMO runs compared with patients with short ECMO runs at a tertiary care ECMO referral center. We retrospectively reviewed all patients on VV ECMO for respiratory failure between August 2014 and February 2017. Bridge to lung transplant, post-lung transplant, and post-cardiac surgery patients were excluded. Patients were stratified by duration of ECMO: extended ECMO, defined as >504 hours; short ECMO as ⩽504 hours. Demographics, pre-ECMO data, ECMO-specific data, and outcomes were analyzed. One hundred and thirty-nine patients with respiratory failure were treated with VV ECMO. Overall survival to discharge was 76%. Thirty-one (22%) patients had extended ECMO runs with an 87% survival to discharge. When compared with patients with short ECMO runs, there was no difference in median age, body mass index (BMI), body surface area (BSA), partial pressure of oxygen (PaO2 )/ fraction of inspired oxygen (FiO2 ) (P/F), and survival to discharge. However, time from intubation to cannulation for ECMO was significantly longer in patients with extended ECMO runs. ( p = 0.008). Our data demonstrate that patients with extended ECMO runs have equivalent outcomes to those with short ECMO runs. Although the decision to continue ECMO support in this patient population is multifactorial, we suggest that time on ECMO should not be the sole factor in this challenging decision.